ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIK SISWA SMK PADA MATERI SISTEM PERSAMAAN LINIER DUA VARIABEL (SPLDV) - Novie Suci Rahmawati; Martin Bernard; Padillah Akbar (Departement of Mathematics Education, 2019)
This study aims to identify and analyze aspects of the communication skills of vocational students in the material system of two-variable linear equations. The samples taken in this study were 5 students from a population of 30 students with different abilities and were taken randomly at one of the West Bandung Vocational Schools, namely class X Computer Engineering Network 2 SMK BINA INSAN BANGSA. The type of research used is qualitative descriptive. The research instrument is a test question of mathematical communication skills in the form of 4 items essays and interviews. Test results that have been carried out on several mathematical communication questions still show results below the average. It can be seen from the percentage of scores per item, namely the question no.1, obtained a percentage of 60% for indicators in explaining ideas, situations orally or in writing with real objects, graphic images, and algebra. Problem no.2 with the acquisition of 35% percentage for indicators to solve problems with the rules used. Question number 3 with the acquisition of a 25% percentage for indicators expressing daily events in mathematical language. Problem no.4 obtained a percentage of 15% for indicators connecting graphs with mathematical ideas. Then it can be concluded that the level of communication skills of vocational students is still not good enough and is classified as low because there are two problem indicators in the low category ≤ 33%